Bank ownership and dynamic capital structure adjustment of firms: evidence from China*. Issue 2 (2nd April 2016) - Zhang, Sheng; Zhang, Keyuan; Zhang, Min
Abstract: Based on a sample of Chinese listed firms from 2006 to 2012, this paper investigates the effect of bank ownership (i.e. firms being shareholders of one or more banks) on the adjustment of a firm's capital structure. The empirical results show that firms holding shares in a bank adjust their capital structure faster than firms not holding shares in a bank. The positive relation between bank ownership and capital structure adjustment is more pronounced when firms provide executives with greater compensation incentives and face more severe financial constraints. Additional tests show that the positive relation between bank ownership and capital structure adjustment only exists in below-target debt firms and firms that hold shares in banks controlled by Chinese shareholders. We also find that firms holding shares in a bank have a smaller disparity between target and actual capital structures, compared with those not holding shares in a bank. Our results provide direct evidence that bank ownership speeds up adjustment toward target capital structure and narrows the gap between actual and target capital structure.